KONTRIBUSI PAJAK DAERAH SEBELUM DAN SESUDAH PEMBANGUNAN MERR TERHADAP PENDAPATAN ASLI DAERAH DI SURABAYA - Rahayu, Lilik Sri; Idayati, Farida (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is aimed to analyze the local tax contribution before and after the development of Middle EastRing Road (MERR) to the Local own source revenue in Surabaya. The object of this research is Local tax city ofEast Surabaya which is influenced by the development of Middle East Ring Road (MERR). The data collectionhas been carried out by conducting interview and documentation. The analysis technique has been carried outby using the analysis of the effectiveness level of local tax and the analysis of local tax contribution. The result ofthis research shows that the effectiveness level of the local tax of East Surabaya in 2011-2015 includes theeffectiveness criteria with its annual average effectiveness is 90.47 percent. It can be stated that the developmentof Middle East Ring Road (MERR) in East Surabaya is able to help to increase the local own source revenue ofSurabaya. The contribution of local tax to the Local own source revenue in Surabaya includes the lack of criteriawith its annual contribution average is 5.56 percent. This is due to the separation of The Local TechnicalImplementation Unit in East Surabaya.Keywords: Effectiveness level, contribution, local tax, local own source revenue, development of MiddleEast Ring Road (MERR)